A Neck Circumference as an Alternative Indicator Screening of Obesity Adolescent: A Scoping Review - -, Zahrina Fildza Luthfiana Sutomo; Yulia Lanti Retno Dewi; Lusi Oka Wardhani (Universitas Islam Negeri Alauddin Makassar, 2025)
Obesity is a fat accumulation condition in the body that causes various health problems including hypertension, diabetes mellitus, coronary heart disease, and the risk of metabolic syndrome. Body mass index is usually used to determine nutritional status in the adolescent group, but it can’t distinguish between fat and muscle mass. Neck circumference is an alternative indicator that can be used to determine adolescent obesity. Neck circumference can describe the accumulation of adipose tissue in the neck, can be used as an indicator of subcutaneous tissue in the upper body, and related to risk factors for cardiovascular disease. This scoping review aimed to evaluate neck circumference used as an indicator of obesity in adolescents, which was expected to provide new insights into the development of indicators in determining adolescent obesity. This review article followed the framework of Arksey and O’Malley and the literature review uses the PRISMA Scr (Priority Reporting Items for Systematic Review Meta-analysis Extension for Scoping Reviews) framework. Three databases used in the article search were PubMed, Science Direct, and Scopus. This review contained five articles cross-sectional studies from Pakistan, India, Brazil, and Bahrain highlighted a significant positive association between neck circumference, BMI, and obesity in children and adolescents, with some studies suggesting that neck circumference was a more accurate screening tool for obesity than BMI. The review study showed that neck circumference was a reliable indicator of obesity in children and adolescents, it had a strong correlation to BMI and can become a more accurate screening tool, particularly with gender-specific cut-offs.